4 Political Ecology and the Event: Calusa Social Action in Early Colonial Entanglements. Issue 1 (2nd July 2018) - Thompson, Victor D.; Thompson, Amanda D. Roberts; Worth, John E.
ABSTRACT: There are many examples of colonial entanglements resulting in shifts in religions, practices, subsistence, and political structures, largely linked to inequalities between the colonized and the colonizers. However, there are also examples in which practices, particularly among Native American societies, persisted in the context of social situations that intertwined peoples with diverse histories. At the time of Spanish arrival, the Calusa of southwestern Florida were a large‐scale, hierarchical society with supra‐community integration and were able to maintain high degrees of autonomy. Our focus here is to explicate the early colonial world of the Calusa. Specifically, we want to understand why early European interactions take such a dramatically different course in southwestern Florida than in other areas of Spanish colonization. To do so we use political ecology and recent scholarship on eventful archaeology to consider Calusa and Spanish social and political action. Our work focuses on interactions between the Spanish and the Calusa during the early and mid‐sixteenth century (ca. 1513 to 1569 CE). We argue that because the Calusa were fisher‐gatherer‐hunters, lacked maize agriculture, and had their capital on the defensible island of Mound Key, Spanish‐Calusa interactions and events transpired in a fundamentally different context compared to other Spanish outposts and colonies. With this example, we show how various events, knowledge, and traditions of the Calusa of southern Florida all worked to create a vastly different colonial entanglement that resulted in the Spanish abandonment of the area for some time.